Non-sensory factors driving the packaging design of ready-to-eat mazamorra morada based on consumer perception - Saldaña, Erick (2021)
Food choice is often influenced by extrinsic factors, which drive consumer perception of a given product or service. It is therefore critical to study them during the design of food packaging. In this context, the aim of this study was to investigate the effect of extrinsic factors on the expected acceptance, purchase intention and holistic perception of consumers of the popular Peruvian dessert mazamorra morada. Twelve stimuli were created by using a fractional factorial design considering packaging material, nutritional information, quality, convenience, and naturalness as factors, previously obtained by open-ended questions. Ninety-seven consumers answered an online survey indicating their expected acceptance, purchase intention and holistic perception. The results showed that the most salient factors for consumers, in terms of expected acceptance, purchase intention, and holistic perception, were packaging material and convenience. For these factors, the levels that increased expected acceptance and purchase intention were the "package made of food grade paper", conveniently adding a "spoon and napkin".